2022
DOI: 10.1186/s12884-022-04416-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gestational diabetes mellitus with maternal age between 35 and 40 years on the metabolite profiles of plasma and urine

Abstract: Background Gestational diabetes mellitus (GDM) is defined as impaired glucose tolerance in pregnancy and without a history of diabetes mellitus. While there are limited metabolomic studies involving advanced maternal age in China, we aim to investigate the metabolomic profiling of plasma and urine in pregnancies complicated with GDM aged at 35–40 years at early and late gestation. Methods Twenty normal and 20 GDM pregnant participants (≥ 35 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…One postdiagnosis study observed a decrease in pyruvate [ 35 ]. Similarly, citrate was found to be higher in in 3 prediagnosis studies [ 15 , 21 , 22 ], 1 at-diagnosis study [ 21 ], and 1 postdiagnosis study [ 15 ] ( Table 1 ). Pyruvate and citrate have been implicated in glucose-stimulated insulin secretion, with pyruvate working to maintain high citrate levels via the reductive carboxylation pathway for the purpose of NADPH production, which supports insulin secretion [ 55 , 56 ] ( Fig.…”
Section: Metabolic Pathways Dysregulated Across Gdm Pregnancymentioning
confidence: 91%
See 3 more Smart Citations
“…One postdiagnosis study observed a decrease in pyruvate [ 35 ]. Similarly, citrate was found to be higher in in 3 prediagnosis studies [ 15 , 21 , 22 ], 1 at-diagnosis study [ 21 ], and 1 postdiagnosis study [ 15 ] ( Table 1 ). Pyruvate and citrate have been implicated in glucose-stimulated insulin secretion, with pyruvate working to maintain high citrate levels via the reductive carboxylation pathway for the purpose of NADPH production, which supports insulin secretion [ 55 , 56 ] ( Fig.…”
Section: Metabolic Pathways Dysregulated Across Gdm Pregnancymentioning
confidence: 91%
“…In further support of dysregulated fatty acid metabolism is the observed alterations in alpha-hydroxybutyrate, a metabolite closely connected to FAO. Alpha-hydroxybutyrate was elevated in 1 prediagnosis [ 25 ], 3 at-diagnosis [ 23 , 26 , 28 ], and 1 postdiagnosis studies [ 15 ] ( Table 1 ). Alpha-hydroxybutyrate has been identified as a marker of the elevated ratio of cytosolic NADH/NAD + , as this metabolite is formed from alpha-ketobutyrate in a reaction that can be catalyzed by lactate dehydrogenase when the cytosolic NADH/NAD + ratio is increased [ 49 , 50 ] ( Fig.…”
Section: Metabolic Pathways Dysregulated Across Gdm Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…The first trimester of pregnancy also included an increased level of xanthine [115], nicotinamide, uridine [113], in the women who later developed GDM. Higher level of citric acid and beta‐alanine were found in the first trimester of GDM pregnancies [116]. Further, ethanolamine and 1,3‐diphosphoglycerate were found to be potential biomarkers of GDM during the first or early second trimester of pregnancy [117].…”
Section: Metabolites Fingerprints Of Gdmmentioning
confidence: 99%